Effect of commensurate lithium doping on the scintillation of two-dimensional perovskite crystals. Issue 7 (27th January 2021) - Maddalena, Francesco; Xie, Aozhen; Arramel,; Witkowski, Marcin E.; Makowski, Michal; Mahler, Benoit; Drozdowski, Winicjusz; Mariyappan, Thambidurai; Springham, Stuart Victor; Coquet, Philippe; Dujardin, Christophe; Birowosuto, Muhammad Danang; et al.
Abstract : Commensurate Lithium doping of two-dimensional lead halide perovskites leads to improved scintillation properties, with enhanced light yield, narrower energy resolution, higher radiation hardness and faster scintillation decay. Abstract : Two-dimensional (2D) hybrid lead bromide perovskites are candidates for high light yield, fast scintillators. In this paper, we discuss the effect of commensurate Lithium (Li)-doping (1 : 1 Li : Pb precursor ratio) on the scintillation properties of two previously reported high light yield 2D-perovskite crystals, PEA2 PbBr4 and BA2 PbBr4 . The effect of Li, e.g. light yield enhancement, is more prominent in PEA2 PbBr4 compared to BA2 PbBr4 . Both perovskite crystals show a broadening of the radioluminescence spectrum and a slightly longer afterglow, with residual scintillation below 2% after 5 s for both materials. The effects of Li on the negative thermal quenching exhibited by the perovskites are also discussed. Li doping increases the light yield of PEA2 PbBr4 by 78% and both perovskite materials show an improvement in their energy resolutions, with a record of 7.7% at 662 keV for the Li-doped PEA2 PbBr4 . Both perovskite crystals also show very fast gamma-ray excited scintillation decays, with average times of 12.9 ns and 8.0 ns for PEA2 PbBr4 and BA2 PbBr4, respectively. This work shows that Li doping brings a significant improvement of the perovskite performance, making the perovskites more competitive for fast, high light yield applications in the medical, security or industrial sectors.